Pengobatan Gratis pada Warga Terdampak Banjir - Tuti Suparyati; Fitrianingsih Fitrianingsih (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2022)
The rainy season with high rainfall in February 2021 occurred. There was a flood disaster along almost the north coast of Java, Pekalongan Regency, Mulyorejo village was one of the villages affected by the severe flood disaster, the flood condition affected the activities of residents, economy, and health. Flooding caused by high rainfall plus unresolved tidal conditions, namely sea levels that are increasing greatly, adding to the severity of the flood situation. The people of Mulyorejo affected by the flood took refuge in refugee camps, the conditions of the evacuation were inadequate with a large number of refugees, causing easy transmission of disease, the number of sick people increased, conditions like this require a helping hand or help from those who care. The purpose of this service activity is to provide health services in the form of free treatment to residents affected by the floods in Mulyorejo village, Tirto District. The method used in this community service activity is a direct method, namely the servant comes to the Mulyorejo village hall to do free treatment. Based on the results of the health examination, most of the villagers suffer from upper respiratory tract infection, hypertention, myalgia, and stomach pain.